FAMILY AND COMPANY SUPPORT IN BREASTFEEDING MOTHER WHO WORK - Nur chabibah; Rini Kristiyanti (Jurnal Ilmu Keperawatan dan Kebidanan, 2020)
Background: Increased female labor is one of the challenges in making the exclusive breastfeeding program successful. Factors that hinder the success of a working mother are short time off work, shorter workplace support, shorter breaks at work, no open space for milking the mother's milk, opposition to the mother's need for increased breastfeeding and production.Objective: To find out the relationship between family support and company support with the performance of working mothers in the Pekalongan Regency.Method: an analytical study related to family and relationships with mother companies in Pekalongan District with cross sectional support. The independent variable in this study is family assistance and company support, while the independent variable is the assistance of working mothers. The population in this study was the study of working mothers in companies in the Pekalongan Regency.Results: analysis with the Chi square test obtained p value of 0.856 ( 0.05) so that it can be concluded that there is no relationship between families support and performance. The analysis with the chi square test obtained a p value of 0.008 (0.05), which concerns the relationship between corporate support and performance resulting in an odds ratio of 7.87, company support that can produce 8 times the consuming performance gets better.Suggestion: Company leaders need to maintain and improve policies for female employees to facilitate breastfeeding, and also need to be provided with lactation rooms that make it easier for mothers to milk breast milk between working hours.